Periodization and self-regulation in action sports: Coping with the emotional load - Collins, D.; Willmott, T.; Collins, L. (Frontiers in Psychology, 2018)
Action sports usually include some danger and personal challenge. The levels of both are often further increased when the sport is placed in a competitive environment. In this paper, we consider the Olympic disciplines of freeskiing and snowboarding in park and pipe. We consider some pertinent theoretical perspectives, then offer some insights on their operation using a range of data from ongoing research and support work. Finally, we offer a number of practical steps which can be taken to optimize performance, both in learning and practicing new tricks and in executing them under the pressures of competition.